Design of an Anti-Intruder Security Sensor on a Home Door Based on the Internet of Things Using a Reed Switch Sensor (Magnetic Door) and a NodeMCU Microcontroller - Muhammad Balkis Delpiero; Muhammad Muttaqin; Hafni (Bahasa Indonesia, 2026)
Home security is an important aspect of modern life, especially in the digital era that demands efficiency and ease of monitoring. The development of Internet of Things (IoT) technology has opened up great opportunities in the development of smart home security systems. Based on these conditions, this study aims to design and implement an Internet of Things (IoT)-based home door security system by utilizing a Reed Switch sensor (magnetic door) and a NodeMCU ESP8266 microcontroller. The Reed Switch sensor functions to detect the door status, both in open and closed states, while the NodeMCU ESP8266 is used as a control center that processes sensor data and sends notifications in real-time via Telegram Bot. The research method used is Research and Development (R&D) which includes the stages of system analysis, design, implementation, testing, and evaluation. The test results show that the system is able to detect changes in door conditions well and send notifications quickly and accurately to users. In addition, the system can operate stably for a fairly long period of time without significant problems. Therefore, the IoT-based door security system developed can be used as an additional security solution that is effective, easy to implement, and economical to improve home security.